Dédale carcéral. Georges Mandel dans le labyrinthe de ses prisons entre la France de Vichy et l’Allemagne nazie (1940-1944) - Christophe Lastécouères (Criminocorpus, 2025)
For four years, between June 1940 and July 1944, Georges Mandel, like other former leaders of the Third Republic (Blum, Daladier and Reynaud), was the target of collaboration between the Vichy regime and Nazi Germany. Very quickly deprived of his freedom, in the summer of 1940 he began a veritable prison journey: placed under house arrest, interned and then imprisoned in a fortress before being deported to Germany and the Nazi concentration camp system. He was also held in more than a dozen sites of detention, resulting in multiple transfers, always staged by the Vichy authorities and the German police (SIPO-SD). The aim of this article is to show, on the basis of private sources deposited by the Mandel family, why itinerancy was an original way of enforcing punishment during the Occupation. In Mandel’s case, this itinerancy was undoubtedly the most destructive of all: for a long time considered an important prisoner, he was no more than a Jewish ‘hostage’ in the eyes of the German authorities when they decided to return him to Vichy in the summer of 1944. It also shows that the prisoner tried to resist his captors by mobilising all his support networks. However, Mandel did not succeed in reversing or even rebalancing this unfavourable balance of power, for two reasons. During his imprisonment, he was unable to maintain his social capital and relationships, which would have enabled him to consider release or escape in France and to remain in detention in Germany, as his return to Paris in July 1944 posed a serious threat to his life. Above all, Mandel’s long itinerancy caused him greater mental wear and tear than other prominent victims of the arbitrary rule of Vichy (Zay) and Nazi Germany (Blum and Reynaud). Even before his return to France and his murder by the Milice, Mandel appeared to be mentally exhausted.